Integration of the Roles of Men and Women in Forming a Harmonious Family - Siti Nur Has Winda; Muhammad Zainuddin Sunarto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to examine how the integration of male and female roles creates a harmonious family within the context of the Arjasa Jatisari Village community in Indonesia. The issue of gender role inequality in the household remains a source of conflict and a decline in the quality of marital relationships. This study used a qualitative approach with a case study method, through in-depth interviews, participant observation, and documentation of five married couples in Situbondo who had been married for more than five years. The results identified three main patterns of role integration in the household: collaborative, adaptive, and traditional. Couples with collaborative and adaptive patterns demonstrated more open communication, shared decision-making, and high emotional involvement, while the dominant traditional pattern often exhibited inequality and double burdens. Role integration practices were found to be stronger in childcare than in domestic work. This study contributes to theories of gender equality and family functionalism, and emphasizes the importance of equal relationship education and policy support in promoting fair and dynamic role sharing in modern households.